1990
DOI: 10.1007/bf00183363
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent dislocation of the elbow

Abstract: Twelve cases of recurrent dislocation of the elbow have been studied with special reference to the cause of instability, the operative findings and the results of treatment. We consider the major cause to be insufficiency of the posterolateral capsule and ligaments, and therefore the best treatment is a posterolateral capsulorraphy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Other clinical studies have indicated that surgery to the LCL may improve the stability in cases of recurrent dislocation. 3,4,25,26 Total for movement (0 to 40 points). Ankylosed elbow: 0 point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other clinical studies have indicated that surgery to the LCL may improve the stability in cases of recurrent dislocation. 3,4,25,26 Total for movement (0 to 40 points). Ankylosed elbow: 0 point.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported recurrent instability of the elbow after a primary traumatic dislocation. [1][2][3][4][5][6][7][8][9][10][11][12][13] The patients complain either of recurrent dislocation or of painful recurrent radiohumeral subluxation which can be reduced by rotating the forearm. 1,7,12,14,15 The instability is related to the degree of disruption of ligaments, described as the circle concept, and termed posterolateral instability (PLI) of the elbow.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,18 The most common cause of an elbow dislocation is a fall on the elbow or outstretched hand from standing height 4,14,19 or higher. 4,15,[18][19][20][21][22][23] The specific mechanisms of coronoid fracture (and elbow dislocation) are varied and can involve twisting and flexion, as well as hyperextension. 5,10,22,24,25 When the elbow is axially loaded in extension, force is concentrated on the articular surface of the coronoid process.…”
Section: Mechanism Of Injurymentioning
confidence: 99%
“…Other complications include osteoarthritis, heterotopic ossification, calcification, instability, pain and parasthesias. 1,22,26 It is not unusual to see degenerative changes on plain radiographs, but they are not necessarily symptomatic. 16 Younger patients tend to experience fewer post-dislocation symptoms.…”
Section: Outcome and Complicationsmentioning
confidence: 99%